YOU'VE GOT A FRIEND. EXPLORING THE ROLE OF FRIENDSHIPS IN THE LIVES OF MEN 80 AND OVER. (11th November 2018) - Gesino, J
Abstract: A 2005 study found that friendships increased life expectancy by as much a 20% (Komaroff, 2016). However, elder men are less likely to utilize friendships and report few if any friendships during late life (Brody, 2016; Olds and Schwartz, 2009). In fact, there is limited information on how men in their eighth and ninth decade of life think and feel about friendships. This paper will report on the findings from interviews with ten men ages 80 to 94 living in a Continuing Care Community that explored the role of friendships in their lives.Consistent with previous research, all of the men identified their wives as their "Best Friends". However, most men reported that their use of friends at this time in their lives met a set of unique and unknown developmental needs of elder men not formerly recognized by gerontologists. These developmental needs met through "friendly relationships"(Matthews, 1986) include: helping men to recognize their own aging, helping them to feel that they are liked and helping them to trust in someone (although not always being able to find that person). Based upon the findings of this study, recommendations for enhancing a "Buddy System" (Greif, 2009) to meet the special unacknowledged needs of men 80 and older will be offered.